Phân tích đa thức thành nhân tử a) x2 +6x +5 b) (x2-x +1) (x2 –x+2) -12

Question

Phân tích đa thức thành nhân tử
a) x2 +6x +5
b) (x2-x +1) (x2 –x+2) -12

in progress 0
Valerie 4 tuần 2021-07-08T19:52:28+00:00 2 Answers 2 views 0

Answers ( )

    0
    2021-07-08T19:53:54+00:00

    Đáp án:

     

    Giải thích các bước giải:

     `a,x^2+6x+5`

    `=x^2+x+5x+5`

    `=x(x+1)+5(x+1)`

    `=(x+1)(x+5)`

    `b,(x^2-x+1)(x^2-x+2)-12`

    `=(x^2-x+3/2-1/2)(x^2-x+3/2+1/2)-12`

    `=(x^2-x+3/2)^2-1/4-12`

    `=(x^2-x+3/2)^2-49/4`

    `=(x^2-x+3/2+7/2)(x^2-x+3/2-7/2)`

    `=(x^2-x+5)(x^2-x-2)`

    `=(x^2-x+5)(x^2+x-2x-2)`

    `=(x^2-x+5)[x(x+1)-2(x+1)]`

    `=(x^2-x+5)(x+1)(x-2)`

    CHÚC BẠN HỌC TỐT

    0
    2021-07-08T19:54:21+00:00

    Đáp án:

     

    Giải thích các bước giải:

     `a,x^2+6x+5`

    `=x^2+x+5x+5`

    `=x(x+1)+5(x+1)`

    `=(x+1)(x+5)`

    `b,(x^2-x+1)(x^2-x+2)-12`

    `=(x^2-x+\frac{3}{2}-\frac{1}{2})(x^2-x+3/2+1/2)-12`

    `=(x^2-x+3/2)^2-1/4-12`

    `=(x^2-x+3/2)^2-49/4`

    `=(x^2-x+3/2+7/2)(x^2-x+3/2-7/2)`

    `=(x^2-x+5)(x^2-x-2)`

    `=(x^2-x+5)(x^2+x-2x-2)`

    `=(x^2-x+5)[x(x+1)-2(x+1)]`

    `=(x^2-x+5)(x+1)(x-2)`

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )